Mengukur tekanan dan jenis mekanisme penyelesaian masalah dalam kalangan pelajar universiti - Fauziah Ibrahim; Nur Athirah Ahmad Zaini; Nazirah Hassan; Ezarina Zakaria; Khadijah Alavi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Excessive levels of academic stress can cause an increased prevalence of health, psychological and social problems. Nonetheless, individuals act differently to stressful situations. This study aims to identify the level of stress and the types of problem solving mechanisms among students in a public university. A quantitative cross-sectional survey was carried out. A total of 100 undergraduate students from the National University of Malaysia, aged between 20 and 27, were selected to participate in the survey. The data were analysed using descriptive statistics. The results demonstrate that majority of participants reported a high level of stress (60%). Furthermore, participant reported eight types of problem solving mechanisms. The ‘cognitive structuring’ and ‘spritual hope’ mechanisms reported the highest mean of 3.32, meanwhile, the ‘self-criticism’ mechanism reported the lowest mean of 1.7. The findings of the study has implications for policy development. It highlights the need for programs that strengthen problem solving among students, including mentor-mentee programme. Also, the administration has to play an important role in reducing stress level among students in the university.